Digital Content Marketing Strategies for Building Brands on MCN Accounts by PT Hoki Adi Karya - Putri, Ester Permata; Rachmawati, Farikha (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2023)
Digital content marketing is now the talk of the world of marketing which is busy being used by all groups, both individuals and business people, to get better profits. PT Hoki Adi Karya or Hakka Indonesia, is one of the companies engaged in the digital academy which facilitates debriefing in the field of digital marketing. The creation of an MCN account managed by Hakka Indonesia is evidence of widespread investment through digital content marketing to enhance brand persona. By using a descriptive qualitative method, the interview approach was carried out to take from the Hakka Indonesia Creative team. The results of this study contain the stages of digital content marketing strategy according to Kotler in building a brand persona. Research findings show that implementing digital content marketing improves the brand persona of MCN accounts